Targeting the Multiple Physiologic Roles of VDAC With Steroids and Hydrophobic Drugs - Rostovtseva, Tatiana K.; Queralt-Martín, María; Rosencrans, William M.; Bezrukov, Sergey M. (Frontiers in Physiology, 2020)
There is accumulating evidence that endogenous steroids and non-polar drugs are involved in the regulation of mitochondrial physiology. Many of these hydrophobic compounds interact with the Voltage Dependent Anion Channel (VDAC). This major metabolite channel in the mitochondrial outer membrane (MOM) regulates the exchange of ions and water-soluble metabolites, such as ATP and ADP, across the MOM, thus governing mitochondrial respiration. Proteomics and biochemical approaches together with molecular dynamics simulations have identified an impressively large number of non-polar compounds, including endogenous, able to bind to VDAC. These findings have sparked speculation that both natural steroids and synthetic hydrophobic drugs regulate mitochondrial physiology by directly affecting VDAC ion channel properties and modulating its metabolite permeability. Here we evaluate recent studies investigating the effect of identified VDAC-binding natural steroids and non-polar drugs on VDAC channel functioning. We argue that while many compounds are found to bind to the VDAC protein, they do not necessarily affect its channel functions in vitro. However, they may modify other aspects of VDAC physiology such as interaction with its cytosolic partner proteins or complex formation with other mitochondrial membrane proteins, thus altering mitochondrial function.